Continous assessment (C. A) practices in Nigerian secondary schools (1998)
In this paper, attempt was made to give the definition of and rational for Continous Assessment in Nigerian secondary schools. The origin, concept and characteristics of C. A were also highlighted. The operational techiques and short-comings of C. A practices in Nigerian secondary schools were discussed. Finally, recommendations to help ameliorate the existing problems in continuous assessment practices in Nigerian secondary schools were suggested.